The use of new types of mineral raw Ukraine in technology ceramic articles with coated - Захаров, Артем Вячеславович (Technology audit and production reserves, 2013)
In the paper in order to save energy and reduce production costs the feasibility of using the domestic quartz-fieldspaar (QFS) has been shown. Research focuses on the use of new import-veneering raw materials in the production of ceramic. Due to convergence of chemical compounds basics and glaze coating products, it is possible to use single-firing technology and to low the temperature to 1100–1150 °C. The efficiency of the marshes as QFS different mineral composition materials of ceramic masses and non-frit coatings has been determined. Based on the previous studies of the mineral composition raw materials, their melting characteristics and firing products phase composition, the ceramic material and glaze coating have been developed. Predicted and experimentally determined operational properties values of the vitrified floor tiles have conformed to the requirements of DSTU B V.2.7-117-2002 and exceeded them in terms of heat resistance (200 °C) and abrasion resistance (0,017 g/cm2). The optimal compositions of ceramics body and glazes on the base of previously unused quartz-fieldspaar raw materials have been obtained. It allowed the current technological and economic problem to be solved.